2006
DOI: 10.1007/s00216-006-0771-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polycyclic aromatic hydrocarbons (PAHs) in environmental samples: a critical review of gas chromatographic (GC) methods

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are frequently measured in the atmosphere for air quality assessment, in biological tissues for health-effects monitoring, in sediments and mollusks for environmental monitoring, and in foodstuffs for safety reasons. In contemporary analysis of these complex matrices, gas chromatography (GC), rather than liquid chromatography (LC), is often the preferred approach for separation, identification, and quantification of PAHs, largely because GC generally affords greater sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
172
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(185 citation statements)
references
References 150 publications
3
172
0
10
Order By: Relevance
“…Among these available studies, the focuses were mainly on the occurrence and distribution of these compounds in coking wastewater, not including their behaviors and fate (e.g., the concentrations of PAHs in various phase states at different stages). It is mainly because of the difficulties in collecting sludge and gas samples and accurately quantifying PAHs in the complicated matrix (Busetti et al, 2006;Poster et al, 2006), so that the systematic balance of these PAHs is not available. As a result, the behaviors and fate of these compounds in coking WWTPs have still not been adequately documented.…”
Section: Introductionmentioning
confidence: 99%
“…Among these available studies, the focuses were mainly on the occurrence and distribution of these compounds in coking wastewater, not including their behaviors and fate (e.g., the concentrations of PAHs in various phase states at different stages). It is mainly because of the difficulties in collecting sludge and gas samples and accurately quantifying PAHs in the complicated matrix (Busetti et al, 2006;Poster et al, 2006), so that the systematic balance of these PAHs is not available. As a result, the behaviors and fate of these compounds in coking WWTPs have still not been adequately documented.…”
Section: Introductionmentioning
confidence: 99%
“…For the quantitative determination of PAHs, gas chromatography (GC), for its high-resolution and sensitivity, is often preferred rather than liquid chromatography (LC). Recently, the wide range of applications of GC-MS technique has been reviewed [25].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by different authors at different locations have shown that average values for the 16 EPA PAHs obtained in environmental samples range between 0.04 and 15.30 ng/m 3 . Sample treatment is usually performed manually; hence it is tedious [19,20] and consumes large amounts of many different solvents if classical PAHs extraction methods are used [20].…”
Section: Introductionmentioning
confidence: 99%
“…The GC -MS methodology provides extensive information on sample composition and enables better compound identification on the basis of structural information. This system records a specified ion at a selected time and confers both better selectivity and better sensitivity [19,20]. Some weak points of this separation and detection technique in PAH determination are mainly co-elution of isomers or structurally similar compounds as well as long chromatographic runs (about 45 -90 min of total analysis time).…”
Section: Introductionmentioning
confidence: 99%